PENGARUH WAKTU TUNGGU DAN WAKTU SENTUH PASIEN TERHADAP TINGKAT KEPUASAN PASIEN POLI UMUM DI PUSKESMAS SUKORAME KOTA KEDIRI - P, Adhesia Est; Puspitasari, Yenny; Rusmawati, Aprin (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Background : The waiting time is the time used to start the list up to the counter medication. While the touch time is the time spent by paramedics both doctors, midwives, nurses to check on patients. From here can be seen the number of visits patients who came for treatment a lot or a little. Based on early studies found a slight problem lingering dissatisfaction of patients on long waiting times and a touch by paramedics in treating patients. Objective : The purpose of this study was to determine the effect of waiting time and time in the patient touch the general level of patient satisfaction in health centers poly Sukorame Kediri. Method : This study uses Corelation. The sample in this study was poly general health center patients Sukorame Kediri, sampling technique used is to use random sampling, the number of respondents were 355 people, collecting data using questionnaires that were tested using the test statistic analysis Ordinal Regression. Result : Based on the results obtained for the wait time 189 respondents (53.2%) and a touch as much as 195 respondents (54.9%) stated the waiting time and the time a patient receives touch very quickly. And patient satisfaction with the outcome as many as 179 people (50.4%) were very satisfied. From the results that have been obtained on the results obtained p-value = = 0.005 p-value α 0.000 and then <0.005, which means no waiting time and time influence the level of satisfaction in touch common poly clinic Sukorame Kediri. Conclusion : The accuracy of the waiting time and the time the touch is a critical factor in providing services and contributing factors of patient satisfaction. And patient satisfaction will also increase the number of patient visits and the confidence to go to the community health center will increase.